Arabic Language Curriculum Development Management at Multilingual Islamic Boarding School: A Case Study of PPM 4 Language Al-Muhibbin - Khoirul Mubin; Muhajir Muhajir; Yayuk Siti Khotijah; Abdul Aziz Khoiri; Mi Guangli (Universitas Muhammadiyah Mataram, 2025)
In the era of globalization, multilingual mastery is a crucial factor in dealing with the dynamics of the world and increasing competitiveness in various sectors, including in Islamic boarding schools. Multilingual boarding schools are Islamic educational institutions that develop the ability to use several languages. The purpose of this study was to examine the development of the Arabic language curriculum at a multilingual boarding school, namely Modern 4-Language Boarding School Al-Muhibbin. This research uses a descriptive qualitative method with a case study approach. Data collection techniques were interviews, observations, and documentation studies. This study found that curriculum development management takes place through three stages: planning, implementation, and evaluation. In the planning stage, the four-language curriculum is systemized into one with rotational cycle management every six months. However, in various activities the use of Arabic is more dominant. Curriculum implementation is supported by the use of structured teaching materials, the use of technology, the application of bi'ah lughawiyyah, and extracurricular programs. Meanwhile, the evaluation stage is conducted formatively and summatively to assess the effectiveness of learning and provide feedback for continuous improvement. The evaluation results show that there is an improvement in students' skills especially speaking and reading skills.